Innovation orientation, market orientation and e-loyalty: evidence from Turkish e-commerce customers - ERGUN, HANDE SİNEM (ELSEVIER SCIENCE BV, 2013)
Present study aims to explore the relationship among e-commerce, market orientation, innovation orientation and e-loyalty. E-commerce usage is becoming more and more widespread among customers. E-loyalty is a useful measurement for e-commerce success, since loyal customers tend to make repetitive purchases which lead to increase in financial performance of the firms. Innovativeness is a core capability for today's highly competitive firms including online ones. Market orientation enables firms to explore, define and meet customer needs; which may in turn drive the innovation orientation. Present model based on these concepts was studied on 376 participants (n=376). In light of the major findings, present article aims to provide managerial implications for customer loyalty in the setting of e-commerce.
Keywords: innovation orientation; market orientation; proactive market orientation; responsive market orientation; e-loyalty; e-commerce; e-commerce success; SATISFACTION; ONLINE; PERFORMANCE; IMPACT